Pengaruh Kualitas Produk, Promosi dan Persepsi Harga Terhadap Keputusan Pembelian di Suisse Bakery - Khaola Irmawati; Suryani Chodidjah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the influence of Product Quality, Promotion, Price Perception, on Purchasing Decisions, the study population is people who have purchased suisse bakery. The proportional sampling technique is simple random sampling with 130 respondents. Primary data were collected through questionnaires using Likert scale models that have been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study simultaneously Product Quality, Promotion and Price Perception on Purchasing Decisions were 66.7%, with Product Quality variables not affecting Purchasing Pecisions and Promotional variables Price Perception variables influencing Purchasing Decisions Suisse Bakery.